2019
DOI: 10.1002/kin.21324
|View full text |Cite
|
Sign up to set email alerts
|

ZnO and TiO2 clusters as catalyst in the addition and abstraction reaction of acrylic acid with the OH radical

Abstract: The present work displays the theoretical analysis on the role of metal oxide clusters as an effective catalyst in the reaction between acrylic acid and OH radical, which has an energy barrier of 12.4 kcal/mol. The formation of metal oxide cluster such as ZnO and TiO2 with varying size from monomer to hexamer is analyzed using cohesive energy, which increases with cluster size. Adsorption of acrylic acid on clusters reveals that dimer ZnO and tetramer TiO2 are good adsorbed entities. The dimer ZnO and tetramer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Acrylic acid (C 3 H 4 O 2 ) is a representative unsaturated short chain fatty acid that can be emitted not only from the production plants of acrylate and some resin products but also from sheep rumen fluid and seaweed. Grudzinskiĭ observed the concentration of acrylic acid in the factory plume to be about 22 to 183 mg m –3 . In addition, some studies have shown that the decomposition of dimethyl sulfoniopropionate in the ocean also produces acrylic acid. , Acrylic acid is widely used in the production of polymers and in the coating of some materials. , As one of the 189 hazardous air pollutants, gas-phase oxidation and liquid-phase radical reactions of acrylic acid have been studied to some extent. The reaction rate constants of acrylic acid with OH radicals, Cl atoms, and ozone have been calculated, and the relevant reaction mechanisms have also been studied by experiments and theoretical calculations. , Moreover, the heterogeneous reaction of acrylic acid on the surface of mineral dust particles has also been studied. For example, Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylic acid (C 3 H 4 O 2 ) is a representative unsaturated short chain fatty acid that can be emitted not only from the production plants of acrylate and some resin products but also from sheep rumen fluid and seaweed. Grudzinskiĭ observed the concentration of acrylic acid in the factory plume to be about 22 to 183 mg m –3 . In addition, some studies have shown that the decomposition of dimethyl sulfoniopropionate in the ocean also produces acrylic acid. , Acrylic acid is widely used in the production of polymers and in the coating of some materials. , As one of the 189 hazardous air pollutants, gas-phase oxidation and liquid-phase radical reactions of acrylic acid have been studied to some extent. The reaction rate constants of acrylic acid with OH radicals, Cl atoms, and ozone have been calculated, and the relevant reaction mechanisms have also been studied by experiments and theoretical calculations. , Moreover, the heterogeneous reaction of acrylic acid on the surface of mineral dust particles has also been studied. For example, Wu et al.…”
Section: Introductionmentioning
confidence: 99%